Pathogenesis and management of Buerger's disease - Liew, Ngoh Chin; Lee, Limi; Nor Hanipah, Zubaidah; Gee, Tikfu; Jabar, Mohd Faisal (Sage Publications, 2015)
Buerger’s disease or thromboangiitis obliterans causes pain, ulceration, or gangrene in the lower or upper extremity. It is associated with chronic cigarette smoking and is believed to be an immune mediated vasculitis. The pathogenesis is still unknown but recent postulate of its association with odontal bacteria has generated much renewed interest. Despite its recognition more than a century ago, little progress has been made in its treatment. Until the pathogenesis is elucidated, abstinence from cigarette is the only effective therapy.